A study of selected factors that may contribute to the incidence of premature infant births in Twelve southwestern Montana counties - Burcham, Genevieve S. (Montana State College, Division of Professional Schools, 1961)
This study was concerned with three selected factors (socio-economic, geographic, and health facilities) that may contribute to the incidence of premature infant births in twelve southwestern counties in Montana. The documentary and exploratory method was employed in securing the data. The results of this study showed no established pattern of the three factors to the incidence of premature infant births.
Keywords: Premature infants